Solve for y -8(y+9)=-40

Math
-8(y+9)=-40
Divide each term by -8 and simplify.
Tap for more steps…
Divide each term in -8(y+9)=-40 by -8.
-8(y+9)-8=-40-8
Cancel the common factor of -8.
Tap for more steps…
Cancel the common factor.
-8(y+9)-8=-40-8
Divide y+9 by 1.
y+9=-40-8
y+9=-40-8
Divide -40 by -8.
y+9=5
y+9=5
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
y=5-9
Subtract 9 from 5.
y=-4
y=-4
Solve for y -8(y+9)=-40

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top